Emotion Understanding Correlates With Parental Emotional Expressivity in Chinese Youths With Hearing Loss and Typical Hearing - Hu, Yousong; Dong, Shuyang; Guan, Fang; Chen, Outong; Chen, Jun; Xu, Shurong (Frontiers in Psychology, 2021)
This study aimed at examining the differences between Chinese youths with hearing loss (HL) and with typical hearing (TH) in emotion understanding (EU), parental emotional expressivity, and the associations between EU and parental emotional expressivity. The participants were 282 youths with HL (14.58 ± 3.42 years old) and 350 youths with TH (11.69 ± 2.49 years old). EU was measured by four visual-mode tasks, of which two involve language comprehension while the others do not. Parents reported positive and negative emotional expressivity on the Self-Expressiveness in the Family Questionnaire. Covariates were controlled for including socioeconomic status, parent gender, youth gender, age, intelligence, and teacher-reported comprehension difficulties. Results showed that the four EU tasks were more challenging for the youths with HL than for the youths with TH. The interaction effect of the two groups × 4 tasks was not significant, suggesting that the differences between the two groups of youths in EU were generally similar across the four tasks. The parents of the youths with HL did not differ from the parents of the youths with TH in how often they displayed positive and negative emotional expressivity. Multigroup regression analyses revealed that negative emotional expressivity was negatively related to EU in the youths with HL but not in the youths with TH. However, these two regression coefficients were not significantly different. Positive emotional expressivity was not related to EU in either group. In conclusion, this study extends the knowledge about the EU of Chinese youths with HL and emotion-related socialization of the parents of these youths.